2014
DOI: 10.1177/1470320314543724
|View full text |Cite
|
Sign up to set email alerts
|

The effects of siRNA-silenced TRPC6 on podocyte autophagy and apoptosis induced by AngII

Abstract: Objective: the objective of this article is to evaluate the role of siRNA-silenced TRPC6 on podocyte autophagy and apoptosis induced by AngII. Methods: mouse podocyte cell lines were cultured in vitro. The apoptosis rates of each group were detected using flow cytometry. The expression of LC3-II protein and changes in distribution were detected by confocal laser, and the western blot protocol was employed for detection of protein expression of LC3-II. Results: AngII-injured podocyte had a significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…The present study supports this hypothesis and identifies a novel Ca 2+ influx pathway involving TRPC6, which is implicated in hypoxia-induced autophagy. Our results are further supported by the recent preliminary observation that silencing TRPC6 by siRNA stabilized angiotensin II-induced autophagy [26]. The role of Ca 2+ influx in the regulation of autophagy remains elusive.…”
Section: Discussionsupporting
confidence: 79%
“…The present study supports this hypothesis and identifies a novel Ca 2+ influx pathway involving TRPC6, which is implicated in hypoxia-induced autophagy. Our results are further supported by the recent preliminary observation that silencing TRPC6 by siRNA stabilized angiotensin II-induced autophagy [26]. The role of Ca 2+ influx in the regulation of autophagy remains elusive.…”
Section: Discussionsupporting
confidence: 79%
“…Intriguingly, TRPC6 expression was found to be up-regulated during podocyte apoptosis 20 . More importantly, silencing TRPC6 inhibits AngII-induced apoptosis in podocytes 21 . The TRPC6-encoding mRNA contains a 3'UTR binding site for miR-26a, and the complementary sequence is evolutionarily conserved among the human, chimpanzee, bushbaby, mouse, and rat mRNA orthologs ( Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…19 The in vivo study showed that TRPC6 mutations would eventually cause Ca 2+ dysfunction and result in glomerular disease. [20][21][22] Therefore, we proposed that FK506 can reduce the intracellular calcium overload by inhibiting TRPC6 expression in podocytes, thereby reducing the podocyte apoptosis and stabilizing the number of podocytes, and further protect the podocytes and decrease proteinuria excretion, whereas the specific molecular pathways still need to be verified by related experiments that will be the research direction in the future.…”
Section: Discussionmentioning
confidence: 99%